Development and characterization of Kevlar/Cocos nucifera L. Sheath/epoxy hybrid composites and graphene nanoplatelet- modified hybrid nanocomposites for ballistic applications - Arockiam, Naveen Jesu (2019)
Kevlar 29 is the most widely used body armor material, since it possesses higher impact resistance compared to other man-made synthetic fibers, such as carbon, glass, etc. Even though Kevlar fabric provides an acceptable range of protection, it is not biodegradable and its manufacturing process is very harmful to the environment. This research has focused on evaluating the effect of hybridizing natural fiber with Kevlar 29 and the influence of adding GNP (Graphene nanoplatelets) on the mechanical, moisture diffusion, morphological, structural, ballistic performance, thermal degradation and viscoelastic properties of laminated composites. Through AHP (Analytical hierarchy process) method, naturally woven novel Cocos nucifera sheath (CS) was identified as a potential natural fiber to be hybridized with Kevlar for body armour applications. Laminated composites were fabricated by incorporating Kevlar and Cocos nucifera sheath layers in the epoxy matrix through hand lay-up method followed by hot pressing. GNP were added with epoxy through ultrasonication process. The mechanical, ballistic, thermogravimetric and dynamic mechanical testing’s were performed as per international standards. The mechanical and moisture diffusion properties analysis revealed that the hybrid Kevlar/CS (75/25) composites exhibited better mechanical and moisture resistance behavior among the hybrid composites. Moreover, addition of GNP improved the tensile, flexural, impact and interlaminar shear properties of laminated composites. However, optimal wt. % of GNP varies with different laminates. Moisture diffusion analysis showed that the laminates with 0.25wt % of GNP content efficiently hinder water uptake by closing all the unoccupied pores inside the laminate. Morphological investigations (SEM and FESEM) have proven that addition of GNP improved the interfacial adhesion and dispersion. Structural (XRD and FTIR) analysis reveals that at 0.25wt% of GNP, all the hybrid composites have shown better crystallinity index and the functional groups presents in the GNP can form a strong interactions with the fibers and matrix. The obtained ballistic results revealed that hybrid composites and CS/epoxy composite panels exhibited similar energy absorption and ballistic limit compared to Kevlar/epoxy composites due to CS’s chemical composition, architecture, and unique shock wave dissipation mechanism. Moreover, addition of GNP improved the energy absorption by 8.5% (nine plies) and 12.88% (12 plies) and the ballistic limit by 4.28% (nine plies) and 6.17% (12 plies), respectively of Kevlar/epoxy/GNP composites at 0.25 wt. %. However, hybrid Kevlar/CS/epoxy/GNP composites and CS/epoxy/GNP laminated composites didn’t show significant improvement after adding GNP. The obtained TGA results showed that Kevlar/CS (75/25) hybrid composites exhibited comparable thermal stability with Kevlar/epoxy composites. Differential scanning calorimetry (DSC) results revealed that hybrid composite offers a virtuous resistance or stability towards heat in the epoxy composites. Viscoelastic analysis results showed that the storage modulus (E’) and loss modulus (E”) of Kevlar/CS (75/25) hybrid composites were higher among the laminates due to improved interfacial interactions and effective stress transfer rate. Also, inclusion of GNP enhanced the thermal stability and viscoelastic properties of hybrid composites due to effective crosslinking which improves the stress transfer rate. Hence, this new ecofriendly material (Cocos nucifera sheath) will efficiently replace Kevlar fabric in the protective applications.